The Accuracy of Serving Performance and Its relationship with some Body Measurements and Bio-Kinematical Variables in Volleyball - Abedulillah, Maher; Shamel, Wesam (Journal of Physical Education, 2011)
The Importance of the Study was lied in the game of Volleyball and its great Development that witnessed these recent years, This development was due to the careful scientific planning and accurate training and other sciences related to sport such as Biomechanics. The problem was the clear weakness in the Performance of The Serving in volleyball for the most of Iraqi volleyball teams generally and especially for the Women teams. The aims of study were Identifying the relationship between the serving accuracy and the Body Measurements and Bio-Kinematical Variables in Volleyball. The Hypothesises of the study were: There is a statistical Relationship between the values of serving accuracy test and the value of some Body Measurements in Volleyball. There is a statistical Relationship between the values of serving accuracy test and the value of some Bio-Kinematical Variables in Volleyball. About The procedures, The Researcher used the descriptive Method, The subject were(12) from the Iraqi Women National team, were conducted in the indoor court of the college of physical education/ University of Baghdad/ Al Jadria. The Researchers concluded that there is a weakness in the Performance of the Serving skill according to the performance of the subject of study in the serving test, and the Body Measurements effect the Bio-Kinematical variables of the serving in volleyball. Finally, The Researchers recommended to making studies in bio-kinematical analysis about some of the basic skills in volleyball using modern and high speed cameras